2016
DOI: 10.1139/cjpp-2015-0573
|View full text |Cite
|
Sign up to set email alerts
|

The myosin activator omecamtiv mecarbil: a promising new inotropic agent

Abstract: Heart failure became a leading cause of mortality in the past few decades with a progressively increasing prevalence. Its current therapy is restricted largely to the suppression of the sympathetic activity and the renin–angiotensin system in combination with diuretics. This restrictive strategy is due to the potential long-term adverse effects of inotropic agents despite their effective influence on cardiac function when employed for short durations. Positive inotropes include inhibitors of the Na+/K+ pump, β… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 68 publications
1
5
0
1
Order By: Relevance
“…Two exploratory electrophysiological studies showed that OM (10 µM) can cause depression of the AP plateau, reduce early repolarization, and shorten ventricular APs in canine myocytes. 23,24 These observations suggest that supratherapeutic concentrations of OM do not prolong canine ventricular APs, a biomarker for delayed repolarization risk. 2 To fully characterize the pro-arrhythmic potential of OM, a battery of in vitro and in silico models were used to evaluate the cardiac safety profile of OM at clinically relevant concentrations.…”
Section: Introductionmentioning
confidence: 95%
See 1 more Smart Citation
“…Two exploratory electrophysiological studies showed that OM (10 µM) can cause depression of the AP plateau, reduce early repolarization, and shorten ventricular APs in canine myocytes. 23,24 These observations suggest that supratherapeutic concentrations of OM do not prolong canine ventricular APs, a biomarker for delayed repolarization risk. 2 To fully characterize the pro-arrhythmic potential of OM, a battery of in vitro and in silico models were used to evaluate the cardiac safety profile of OM at clinically relevant concentrations.…”
Section: Introductionmentioning
confidence: 95%
“…The clinical efficacy and safety profile of OM have been demonstrated, 20,22 however, a CiPA‐based assessment for OM has not been performed. Two exploratory electrophysiological studies showed that OM (10 µM) can cause depression of the AP plateau, reduce early repolarization, and shorten ventricular APs in canine myocytes 23,24 . These observations suggest that supratherapeutic concentrations of OM do not prolong canine ventricular APs, a biomarker for delayed repolarization risk 2 .…”
Section: Introductionmentioning
confidence: 98%
“…Myosin head detachment rate (i.e., k det ) has been identified as a key parameter influencing contractility because it determines the time myosin is bound to actin in a force producing state (Janssen, 2010;Greenberg et al, 2014;Sung et al, 2015;Liu et al, 2018). The discovery of a host of cardiomyopathy mutations and a new generation of chemical compounds that modify myosin "motor" kinetics and chemomechanical processes (Malik et al, 2011;Spudich, 2014;Tardiff et al, 2015;Nanasi et al, 2016Nanasi et al, , 2018Swenson et al, 2017;Kampourakis et al, 2018;Mamidi et al, 2018), which produce divergent effects on force and velocity suggest that revival of the term clinotropy (i.e., velocity) should be considered in order to more holistically define the term contractility as force (i.e., intoropy) and velocity (i.e., clinitropy) (MacLeod, 2016). Myocardial contractility should be defined as the load and length-independent, kinetically controlled, chemo-mechanical processes responsible for the development of force (inotropy) and velocity (clinotropy).…”
Section: (See Footenote 1)mentioning
confidence: 99%
“…A fenti feltétele-zést részben in vivo tanulmányok is megerősítették (25,28). Terápiás OM-koncentrációk mellett a szívizomsej-tek intracelluláris Ca 2+ -anyagcseréje és ingerlékenysé-gi folyamatai várhatóan nem fognak jelentősen módo-sulni (39,40). Az újabb adatok és saját eredményeink alapján az OM hatásmechanizmusa azonban némileg újragondolásra szorul.…”
Section: Klinikai Vizsgálati Eredmények Omecamtiv Mecarbillalunclassified